2023
DOI: 10.47197/retos.v49.99154
|View full text |Cite
|
Sign up to set email alerts
|

Improving the psychophysiological condition of secondary school learners through the Olympic education program during the Covid-19 pandemic

Yaroslav Galan,
Yuriy Moseychuk,
Yurii Dutchak
et al.

Abstract: The article aims to evaluate the impact of the proposed "Olympic Education" program on the physical and psycho-emotional state of middle school children. Materials and methods. We conducted research in Chernivtsi specialized schools, and 34 children aged 13-14 participated in the experiments. We tested effectiveness experimentally. A group of 16 boys and 18 girls were involved in the extracurricular activities based on the proposed program. Results. The results of the transformative experiment proved that impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Our research does not contradict the results obtained by other scientists (Yarmak et al, 2017;Mondéjar-Jiménez et al, 2022;Lacoste et al, 2020;Carter-Thuillier et al, 2022). Many previous studies have confirmed the importance of physical activity and psychological well-being for overall health and well-being (Poblete-Valderrama et al, 2023;Galan et al, 2023). Our program for correcting the physical and psychoemotional state of female students supports and expands these results, providing an innovative approach to integrating physical and psychological aspects of health.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our research does not contradict the results obtained by other scientists (Yarmak et al, 2017;Mondéjar-Jiménez et al, 2022;Lacoste et al, 2020;Carter-Thuillier et al, 2022). Many previous studies have confirmed the importance of physical activity and psychological well-being for overall health and well-being (Poblete-Valderrama et al, 2023;Galan et al, 2023). Our program for correcting the physical and psychoemotional state of female students supports and expands these results, providing an innovative approach to integrating physical and psychological aspects of health.…”
Section: Discussionsupporting
confidence: 84%
“…This study focuses on the specific challenges faced by female students who are actively engaged in roles supporting migrant children. As a result of the forced migration of students and the consequences of the Covid-19 pandemic, many social, political, and psychological problems are worsening (Lacoste, et al, 2021;Intelangelo et al, 2022;Bürgin et al, 2022;Galan et al, 2023). Both children and student youth suffer the most in this situation since the stress of being in a military conflict zone, resettlement, and adaptation to new living conditions can negatively affect personality development and mental and physical health.…”
Section: Introductionmentioning
confidence: 99%